Egyéni panaszzsoltárok jelentősége az istentiszteleti gyakorlatban - KOVÁCS, Enikő Hajnalka (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2023)
The Importance of Individual Lament Psalms in Worship Practice The theological significance of individual lament songs lies primarily in their giving voice to suffering. Despite the complaint, the sufferer does not turn away from God since the centre of human existence is God. Suffering does not rule out the connection with God but rather confirms it. The lament has by now lost its original meaning and has received a negative report, as in the eyes of today’s humanity complaint is an expression of unbelief and a distrustful attitude. This aspect, the importance of lament songs, has been ignored by scholars until now. However, the predominance of lament songs in the Book of Psalms means that the issue of complaint is not something marginal or unusual but an important element of faith. One of the most important characteristics of this genre is the sudden change of mood, when the complaint unexpectedly turns into praise. This poetic form involves the transition from hopelessness to joy, for the form not only contains a description of the problem but also the solution to it as well. In a world that has become desensitized, it is important to use these psalms.